Development of a Local Sundial Based Chronotype Measurement Tool from the Google Prayer Times Application - Yusuf Alam Romadhon (Urecol Journal. Part E: Engineering, 2021)
Introduction: In previous studies a chronotype questionnaire has been compiled using a prayer time benchmark as a measure to determine whether a person's waking or sleeping behavior is categorized as early or late. The use of questionnaires based on patient answers regarding the question of how many hours from the evening prayer time (definitive night) and dawn time (the dawn twilight) does not rule out the possibility of recall bias. Therefore, it is necessary to develop a chronotype measuring tool based on the Google Prayer Schedule application, to calculate how long from the critical point the correspondence of a sundial with a person's waking time. Purpose: Develop a sundial based chronotype measuring tool from the google application for local prayer schedules. Method: Use of a questionnaire containing waking hours, hours of sleep on weekdays and holidays, to then calculate the difference from the critical time of the sun, namely the difference with the time of sunrise and the definitive hour of the night from the google application local prayer schedule where the respondent lives. Definitively, as in previous studies, 7 items were developed, relating to these habits. Respondents filled out via google form for questions from the questionnaire. Calculation of the difference between waking/sleeping hours and definitive sunrise/night hours by researchers. The research was conducted in the period November - December 2020. Results: There were 795 respondents who participated in this study. Analysis of the 6 questions, the results of the item-total correlation were sequentially with the value of r, 0.759; 0.690; 0.883; 0.761; 0.740; 0.908 with an overall p value of 0.000. Cronbach's alpha value = 0.877. Conclusion: the chronotype questionnaire based on the distance between the hours of sleep/wake up and the midpoint of sleep relative to the rising time, curfew, midnight point, is concluded to be valid and reliable.